Colonización vaginal y anorectal por el streptococo beta hemolito del grupo B en gestantes con amenaza de parto pretérmino y ruptura prematura de membranas que acuden a los Hospitales Manuel Ygnacio Monteros Hospital Isidro Ayora de Loja periodo enero agosto 2013. - Requelme Loján, Rosa Amalia. (2013)
Β -hemolytic streptococcus group B, is a colonizing the urogenital and gastrointestinal tract. In pregnant this bacterium colonizes the genital tract contributing to the occurrence of preterm birth , premature rupture of membranes and neonatal infection. The main objective stated in the research was: To determine the frequency , risk factors and anorectal and vaginal colonization by group B beta-hemolytic streptococcus in pregnant women with Threatened Preterm Premature Rupture of Membranes and attending hospitals " Manuel Ygnacio Monteros Hospital Isidro Ayora Loja " . Period January-August 2013 . This research was conducted in the months of March to August 2013 , is a prospective, descriptive cross-sectional study conducted in pregnant women of 32-36 weeks and Threatened Preterm Premature Rupture of Membranes hospital services in Gynecology Obstetrics hospitals : Manuel Ygnacio Monteros Valdivieso, Isidro Ayora Hospital of Loja , the sample was made up 160 pregnant women, in which a swab sample of the outer third of the vagina and anorectal region for subsequent culture was taken . The results were : 160 pregnant women studied GBS was isolated in 38 pregnant women ( 23.75% ) , of which (68.42 %) were preterm labor ( 31.57% ) Premature Rupture of Membranes being more frequent vaginal colonization (52.63 %).The Obstetric-Gynecologic history and the most important complication in pregnant women with preterm labor in the current pregnancy was urinary infection. The results suggest a strategy of prevention based on vaginal cultures as rectal in pregnant women with preterm labor and Premature Rupture of Membranes, because in the present study a relatively high (23.75%) colonization is demonstrated, for this reason it is important to identify the population of pregnant women with GBS in order to prevent complications in pregnancy and decrease perinatal transmission taking behaviors inherent in the management and prophylaxis of GBS carrier mothers.